P-185 Whole system end of life strategy. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Stevens, Alison; Lew, Eva
Abstract : Our hospice leads the End of Life Locality Group within our Clinical Commissioning Group (CCG) area. The CCG End of Life Strategy (EOL) was due for renewal so it was agreed to develop a 'whole system' strategy led by the hospice including the CCG, all providers with a key responsibility in delivering end of life care and service users. The aim of this was to adopt a consistent approach to meeting local need, pooling resource and sharing best practice, resulting in a better end of life experience for people within the locality. A project planning group was set up and looked at local needs as well as national drivers. The group decided to adopt the national Ambitions for Palliative and End of Life Care as the overarching framework for the strategy. The locality group hosted four 'Transforming End of Life Care' whole system workshops with 193 attendees across all providers to identify gaps in service delivery and areas of best practice. Knowledge gleaned from these workshops fed into the local actions that were allocated to each ambition and a high level action plan was embedded within the strategy. This strategy and high level action plan now drives the actions of five locally based workstreams, each with a lower level action plan, clearly identified outcomes and measurements to ensure the overall strategy is delivered. Ongoing evaluation is undertaken by the Locality group. During the strategy planning phase there were a number of external changes that occurred including the decision by NHS England to introduce the 'Success regime' to Essex. The group used this as an opportunity to share the strategy with the other CCGs involved and it was adapted and used as the framework across a wider area to influence good practice and improve experiences for patients and their families.